(untitled) (Global Journal of Management and Business Research, 2012)
The Nigerian stock market have operated using the call-over system since inception, however, the call over system of trading was effective in handling the for few market transaction of the time. The emergence of a large trading facility as a result of the privatisation and the commercialisation of the hitherto government stock made the system feeble and unable to handle large transaction in the market, thus, necessitating the macrostructure change to the Automated Trading System (ATS) in 1999. Survey method using structured questionnaire was adopted for the study. It was revealed that the ATS was an effective trading system. The system brings about an efficient settlement system and foster new trading opportunities. It was recommended that to reduce human interference in the market further internationalisation of the market should be encouraged.